Pelatihan Peningkatan Kemampuan Berkomunikasi Menggunakan Bahasa Inggris Dalam Memberikan Pelayanan Prima Pada Industri Perhotelan di Balikpapan - Elisabeth Milaningrum; Patria Rahmawati; Zulkifli Zulkifli; Subur Mulyanto (Abdimas Universal, 2019)
The growth of hotel in Balikpapan quickly must be balanced with the improvement of hotel employees’ competence in hospitality industry along with the increasing of foreign countries guest that is needed excellent service in order to fulfill the guests satisfaction. Communication is one of the most importantant aspect while giving excellent service to the guests especially to foreign countries guest that demand all of the hotel employees can communicate in English fluently. The probles that was found for our community service partner was the low English communication competence of hospitality employee therefore they cannot give excellent service. Method that used to solve the problem was done through 4 steps, such as: preparation, problem formulation, implementation that consists of English training and mentoring, and evaluation program. Based on the result of our community service that has followed by 40 hospitality employees, it can be concluded that there is significant progress of English communicative competence for each hospitality employee tha has followed English training and also based on the result of mentoring and evaluation, it is stated that this community service programe through English training for giving excellent service can help hospitality employees to increase their self confidence while communicate with foreign countries guest.